2000
DOI: 10.1002/1097-4636(20001205)52:3<447::aid-jbm2>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology and wear mechanisms of four clinically relevant biomaterials after hip simulator testing

Abstract: The surfaces of worn components hold clues to the underlying wear mechanisms. Previous evidence suggested that the absolute wear rates of acetabular components in a hip simulator were related to mechanical behavior; we hypothesized that the surface morphology of the liners might also be sensitive to mechanical properties. A noncontact, three-dimensional surface topography measurement system based on white light interferometry was used to quantify the surface morphology of ultra-high molecular weight polyethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Furthermore, by quantitatively analyzing the surface data, the roughness and waviness can be quantified and compared with as-manufactured components, thereby providing insight into the magnitude of surface changes that occur in vivo. 8 10 Ultimately, quantitative measurements of implant surfaces are used to validate in vitro and computational models that seek to simulate in vivo wear processes.…”
Section: White Light Interferometrymentioning
confidence: 99%
“…Furthermore, by quantitatively analyzing the surface data, the roughness and waviness can be quantified and compared with as-manufactured components, thereby providing insight into the magnitude of surface changes that occur in vivo. 8 10 Ultimately, quantitative measurements of implant surfaces are used to validate in vitro and computational models that seek to simulate in vivo wear processes.…”
Section: White Light Interferometrymentioning
confidence: 99%
“…Macroporous EH scaffolds were prepared using a leachable porogen strategy. Briefly, macroporous networks were fabricated by incorporating a NaCl porogen (70,75, and 80 wt%) into the EHD monomer solution prior to cross-linking. EH networks were formed around the crystals by radical polymerization, and the porogen was removed by water leaching.…”
Section: Eh Networkmentioning
confidence: 99%
“…Polyacetals have also been used clinically in several orthopedic implants, most notably the Freeman all-polymer knee replacement and hip resurfacing prostheses (73,74). Current studies have discussed work on surface wear of hip joints and mechanical properties of these materials (73)(74)(75). A recent study published by Lee and Choi demonstrated that the properties of a porous polyacetal block were similar to that of bone (76).…”
Section: Polyacetals and Polyketalsmentioning
confidence: 99%
“…Alternative methods to measure wear directly were also developed including observing shape change through contact profilometry and using co-ordinate measuring machines (CMM) 5 and optical methods such as holography, white light interferometry and shadow graphs. 68 Osteolysis, the primary cause of revision in metal-on-polyethylene bearings, 9 was recognised to be caused by the cellular response to the polyethylene wear particles. 10 The size and volume of these polyethylene particles have more recently been shown to further influence cell behaviour 11 suggesting that while polyethylene wear rates indicated polyethylene loss, they do not necessarily fully predict clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%